The Influence of Roles and Management Functions of Head Nurses on Nursing Outcomes as Perceived by Professional Nurses at a General Hospital, Regional Health 1 - Puangchan, Kanlaya; Suntayakorn, Chanjar (NU Journal of Nursing and Health Sciences, 2019)
The purposes of the descriptive research were: 1) to investigate the roles and management functions ofhead nursesas perceived by professional nurses, 2) to investigate the nursing outcomes as perceived by professional nurses, and 3) to explore the influence of roles and management functions of head nurseson nursing outcomes at a general hospital,Regional Health1. The335 professional nurses who providing nursing care in a general hospital,Regional Health 1. Multistage random sampling was used for selecting the sample. This research tools were the questionnaires which be comprised to three parts: 1) demographic data, 2) roles and management functions of head nursesas perceived by professional nurses, and 3) the nursing outcomes as perceived by the professional nurses. These questionnaires were tested for reliability and validity. The Index of concurrence was between 0.8 and 1. The Cronbach's alphareliability coefficients of part 2 and 3 were .98, 0.98 respectively. Data were analyzed by descriptive statistics(percentage, mean,standard deviation), Pearson's product moment correlation Coefficient and Multiple regression The research findings were as organized follows. 1Professional nurses perceived the roles and management functions of head nurseat the high level ( = 3.90, SD = .52). 2) Professional nurses perceived the nursing outcomes at the high level ( = 3.99, SD = .51). Finally, 3) the roles and management functions that statistically significant to predict the nursing outcomes were controllingand organizing (p < .01). These predictors accounted for 67.80 % (R2 = .678).